EKSISTENSI PENGADILAN NEGERI DALAM PENYELESAIAN SENGEKETA ADAT DI BALI - Mita Dwijayanti (Fakultas Hukum, Universitas Muhammadiyah Pontianak, 2019)
Customary disputes are part of customary conflicts, whether the subjects are individuals or groups of people as a community, known as indigenous peoples in the form of traditional banjars. Based on article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) that the Indonesian nation is a rule of law, the consequence of a rule of law in Indonesia is that everything must be regulated in law. The enactment of written law in Indonesia causes the recognition of the rights of indigenous peoples in Indonesia to be recognized in writing in the Constitution, namely Article 18 B of the 1945 Constitution. If referring to article 18B paragraph (2) which formulates